DNA Computing and Its Application on NP Completeness Problem - Hasudungan, Rofilde; Rohani, Abu Bakar; Rozlina, Mohamed (2013)
Abstract. DNA computing is emerging research area that attracts many researchers in multidiscipline area range from biology, physics, mathematics, and computer science. Nowadays, many researchers already solved problem using this technique, mostly classified as NP (Nondeterministic Polynomial) problem since the inheritance of DNA computing in processing simultaneously and it huge memory capacity. Despite very promising, DNA computing faces several obstacles such as exponential solution explosion, representing weight etc. This paper aim is to give a review on current achievement on DNA computing upon NP-completeness problem.